Sojourners and strangers: the doctrine of the church - Allison, Gregg R. (Foundations of evangelical theology series, 2012)
The intention of the Foundations of Evangelical Theology series is "to address all areas of evangelical theology with a special emphasis on key issues in each area" and "to incorporate insights from Scripture, historical theology, philosophy, etc., in order to produce an up-to-date work in systematic theology." (17) Most of the writers are thoroughly evangelical in their theology and from a broadly Reformed perspective. The series aims to be "understandable to the beginner in theology as well as to the academic theologian," so the authors take care "to define whatever technical terms they use." (17) With that in mind, Gregg Allison is offering a textbook on ecclesiology which is evangelical and broadly Reformed. Allison teaches at Southern Baptist Theological Seminary, so it`s a Reformed baptist perspective. He is an elder at Sojourn Community Church, and if you`re familiar with that church/church planting network, that means this is an ecclesiology from a Reformed Baptist perspective that is in favor of multi-site churches (which he provides a defense for at the end of chapter 9).